The attitudes of physicians toward nurse prescribing rights: a cross-sectional study - Yu Wu; Jian Liu; Lovel Fornah; Zeping Yan; Lijun Meng; Shicai Wu (BMC Nursing)
Abstract Background Nursing prescribing rights have been proposed in many countries, with physicians’ attitudes playing an important role. This study aimed to investigate the attitudes of physicians toward nurse prescribing rights. Methods A cross-sectional study of 112 Chinese physicians was conducted from January to March 2024. This study utilized a demographic information form, nurses’ prescription right knowledge questions, and a scale to measure nurse-physician collaboration. The data was analyzed with IBM SPSS-21 software using descriptive and inferential statistics. We used the mean±standard deviation, frequencies and percentages to describe the demographic information, T-test, Chi-square test or Fisher’ s exact test, and binary logistic regression analysis to analyze the correlated factors of the attitudes of physicians toward nurse prescribing rights. Results Of 112 physicians, 60 supported nurse prescribing rights, accounting for 53.57% of the total. The results of the single-factor analysis indicated significant differences in the aspects of sex. The binary logistic regression revealed that being female (OR = 0.195, 95%CI = 0.072 ∼ 0.529), having knowledge of nurse prescribing rights (OR = 1.513, 95%CI = 1.051 ∼ 2.176), and promoting nurse-physician collaboration (OR = 1.058, 95%CI = 1.032 ∼ 1.084) were the factors that correlated with physicians’ attitudes toward nurse prescribing rights. Conclusions Most physicians expressed a favorable attitude toward nurse prescribing rights. The results of this study will help advance the development of nurse prescribing rights and ultimately improve the quality of patient care.